THE POTENTIAL OF ENGLISH LEARNING VIDEOS IN FORM OF VLOG ON YOUTUBE FOR ELT MATERIAL WRITERS - Rezza Anugerah; Yohanes Gatot Sutapa Yuliana; Dwi Riyanti (ICoTE Proceedings, 2019)
YouTube is the most popular video sharing websites where millions of videos can be found online, especially videos for learning a language. Students can use YouTube to get many language learning videos to help them study the language. Not only getting many videos that can be used as teaching materials in the classroom, teachers can also create their own English video for their students or even for everyone. Designing an English learning video is an opportunity for teachers to make videos based on their teaching context. One type of content that can have a big opportunity to develop is English learning video in form of Vlog. Vlog has a huge number of audiences, especially for Indonesian learners. This research is aimed at analyzing the potential of English learning video in form of Vlog for ELT material writers.